Budgeting in Bulgaria - Hawkesworth, Ian (OECD Publishing, 2010)
Bulgaria's budget management has seen a series of structural and procedural reforms, including in budget execution, treasury functions, internal audit, and programme and medium-term budgeting. This article discusses the use of modern budgeting techniques in Bulgaria such as top-down budgeting, multi-year budgeting perspectives and the use of performance information in the budget process, and makes recommendations for budget formulation, the role of Parliament, budget execution and management (including organisational questions and the role of municipalities), and accounting and audit
Keywords: Finance and Investment; Governance; Bulgaria